Influence of control parameters on the crack paths in the aluminum alloy 2024 under bending (Fracture and Structural Integrity, 2015)
The paper presents development of crack paths in aluminium alloy 2024. Fatigue tests were carriedout for specimens with rectangular cross-section. The specimens were put to bending at controlled energyparameter amplitude and bending moment amplitude. The proposed method of conducting research with thecontrolled energy parameter has been presented in [1]. The energy parameter model proposed by Macha hasbeen used in the tests. Tests with controlled energy parameter amplitude allow observing crack growthdepending on maximum shearing stress surface. Tests with controlled bending moment amplitude allowedobserving two types of crack paths.
Keywords: Energy parameter